Pengaruh Gaya Kepemimpinan Dan Komunikasi Interpersonal Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Kantor Bupati Pasaman Barat - Lutfi, M.Haikal; Sari, Marta Widian; Sari, Yosi Puspita (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of leadership style and interpersonal communication on employee performance, with job satisfaction as an intervening variable at the Office of the Regent of West Pasaman. The background of this study is based on the suboptimal performance of public servants, low levels of job satisfaction, and communication gaps between leaders and subordinates that affect organizational effectiveness. This research employs a quantitative approach using a survey method, where primary data were collected through the distribution of questionnaires to employees of the Office of the Regent of West Pasaman. The sampling technique was determined using an appropriate method based on the characteristics of the research population. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to examine both direct and indirect effects among variables. The results indicate that leadership style and interpersonal communication have a positive and significant effect on job satisfaction. Furthermore, job satisfaction also has a positive and significant effect on employee performance. Leadership style and interpersonal communication were found to influence employee performance both directly and indirectly through job satisfaction as an intervening variable. Thus, job satisfaction is able to mediate the relationship between leadership style and interpersonal communication and employee performance. This study is expected to contribute theoretically to the development of human resource management science, particularly regarding the role of job satisfaction as an intervening variable, and to provide practical recommendations for the Office of the Regent of West Pasaman in improving employee performance through the implementation of appropriate leadership styles and the strengthening of effective interpersonal communication